Car Custodians: Reflexive Automobilization under and in the eye(s) of FDM 1 - Beckmann, Jörg (Proceedings from the Annual Transport Conference at Aalborg University, 1999)
In this PH.D-project, I address, what I call, the risks of automobilization. I ask why motorization, noise and air pollution, the degradation of the environment and the destruction of urban and rural landscapes are still increasing, despite the fact that both “experts” and “non-experts” have acquired knowledge about the causes and reasons of such threats. In order to reveal the hidden mechanisms behind the reflexive actions of both transport “experts” and “non-experts” and in order to reveal how the risks of automobilization are socially constructed, I refer to the German concept of the “Leitbild”2 . The Leitbild as an analytical instrument is commonly used both in the sociology of technology and science as well as within politics and every-day-life in Germany. With respect to the research issue at stake a “mobility Leitbild” expresses a cultural perspective on spatial mobility and results from an interference of both expert and lay knowledge on transport and mobility. In other words it is just as much a product of reflexive processes amongst the actors within transport and mobility as it shapes and underpins the social and cultural construction of automobilization risks. For the purpose of unfolding the expansion of one out of many possible mobility Leitbilder in Denmark, I will focus on the Danish Automobile Owners Association (Forenede Danske Motorejere – FDM). In order to show how a particular type of mobility Leitbild has expanded and how this Leitbild has formed the responses towards the risks of automobilization, I refer to FDM’s monthly magazine MOTOR. Apart from an analysis of relevant articles found in the issues from 1962 to 1997, the focus of the empirical work lies on the title pages of MOTOR. By employing qualitative and quantitative methods of picture analysis, I intend to show how the social construction of automobilization risks is intertwined with the mobility Leitbild of this club.